TECHNOLOGY OF DRIP IRRIGATION OF VINEYARDS - Hudayev, Ismail; Khujakulov, Rustam (Innovatsion texnologiyalar, 2023)
The article discusses the issues of rational use of water resources in conditions of water scarcity around the world, rational use of water in the cultivation of crops, the use of drip irrigation technology in the Bukhara region for irrigation of vineyards, which is an economical way of irrigation. One of the most promising areas of providing the population with high-quality and abundant agricultural food is the use of drip irrigation technologies for irrigation of agricultural crops. Based on the analysis of the results of field and laboratory experiments conducted by the authors and the results of scientific research obtained over the next 5 years, when using drip irrigation technology at the experimental site, the maximum field moisture capacity of the soil, the quantity of irrigation and irrigation norms for the vineyard are recommended.